Muslim Political Theology Before and After Empire: Shāh Muḥammad Ismāʿīl’s Station of Leadership (Manṣab-i Imāmat) - Tareen, SherAli (Political theology, 2020)
This essay examines an important yet hitherto unexplored early-nineteenth century Indo-Persian work of Muslim political theology Station of Leadership (Manṣab-i Imāmat; also known as Darājāt-i Imāmat), written by the towering and contentious Sunnī thinker and political theorist from Delhi Shāh Muḥammad Ismāʿīl (d. 1831). In this hugely critical though lesser known of Ismāʿīl’s texts, he sought to detail a theory and framework of ideal forms of Muslim political orders and leaders. Manṣab-i Imāmat presents a fascinating example of a text of Muslim political theology composed during a moment marked by a crisis of sovereignty as South Asia gradually yet decisively transitioned from Mughal to British rule. In this essay, through a close reading of Manṣab-i Imāmat, I aim to bring into view a vision of Muslim political thought and understanding of sovereignty that exceed and subvert the modern privileging of a territorial conception of the nation-state as the centerpiece of politics. I show that while tethered to an imperial Muslim political theology that assumed Islam’s superiority over and subsumption of other religious identities and traditions, sovereign power for Ismāʿīl indexed not territorial sovereignty but the maintenance of Muslim markers of distinction in the public performance of everyday religious life.